Bromodomain protein BRD4 controls HOTAIR, a long noncoding RNA essential for glioblastoma proliferation - Pastori, Chiara; Philipp Kapranov; Clara Penas; Veronica Peschansky; Claude-Henry Volmar; Jann N. Sarkaria; Amade Bregy; Ricardo Komotar; Georges St. Laurent; Nagi G. Ayad; Claes Wahlestedt (Proceedings of the National Academy of Sciences - PNAS, 2015)
Bromodomain and extraterminal (BET) domain proteins have emerged as promising therapeutic targets in glioblastoma and many other cancers. Small molecule inhibitors of BET bromodomain proteins reduce expression of several oncogenes required for Glioblastoma Multiforme (GBM) progression. However, the mechanism through which BET protein inhibition reduces GBM growth is not completely understood. Long noncoding RNAs (lncRNAs) are important epigenetic regulators with critical roles in cancer initiation and malignant progression, but mechanistic insight into their expression and regulation by BET bromodomain inhibitors remains elusive. In this study, we used Helicos single molecule sequencing to comprehensively profile lncRNAs differentially expressed in GBM, and we identified a subset of GBM-specific lncRNAs whose expression is regulated by BET proteins. Treatment of GBM cells with the BET bromdomain inhibitor I-BET151 reduced levels of the tumor-promoting lncRNA HOX transcript antisense RNA (HOTAIR) and restored the expression of several other GBM down-regulated lncRNAs. Conversely, overexpression of HOTAIR in conjunction with I-BET151 treatment abrogates the antiproliferative activity of the BET bromodomain inhibitor. Moreover, chromatin immunoprecipitation analysis demonstrated binding of Bromodomain Containing 4 (BRD4) to the HOTAIR promoter, suggesting that BET proteins can directly regulate lncRNA expression. Our data unravel a previously unappreciated mechanism through which BET proteins control tumor growth of glioblastoma cells and suggest that modulation of lncRNA networks may, in part, mediate the antiproliferative effects of many epigenetic inhibitors currently in clinical trials for cancer and other diseases.